2023
DOI: 10.1111/spol.12897
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, skills or social mobility? Citizens' perceptions of the purpose of education

Abstract: This article explores individual views of the purpose of education. Most existing research focuses on attitudes and policy preferences; while these types of perceptions have so far been largely overlooked due to a lack of data. Our analysis of original survey data in eight Western European countries shows that personal socioeconomic factors and ideological predispositions shape these individual opinions. Individuals with higher levels of education and income are more likely to view education as aimed at expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The policy feedback literature emphasises the influence of policies and their impact on politics (e.g., Béland, 2019; Béland et al, 2019, 2022; Busemeyer & Guillaud, 2023; Korpi & Palme, 1998; Pierson, 1993; Schneider & Ingram, 2019; Skocpol, 1992; Vannoni, 2019). However, delving into the cumulative effects of multiple policies presents a considerably more complex challenge (Lahat & Sened, 2023; Dery, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The policy feedback literature emphasises the influence of policies and their impact on politics (e.g., Béland, 2019; Béland et al, 2019, 2022; Busemeyer & Guillaud, 2023; Korpi & Palme, 1998; Pierson, 1993; Schneider & Ingram, 2019; Skocpol, 1992; Vannoni, 2019). However, delving into the cumulative effects of multiple policies presents a considerably more complex challenge (Lahat & Sened, 2023; Dery, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Feedback includes people's (voters') preferences in a circular pattern affected by learning and past policies. Policies affect behaviours and create social outcomes that, in turn, create new desires, needs, and claims that translate into new policy preferences and new or adapted policies (Busemeyer & Guillaud, 2023; Korpi & Palme, 1998; Pierson, 1993; Skocpol, 1992; Vannoni, 2019). In other words, policies influence politics (Béland et al, 2019; Schneider & Ingram, 2019) and vice‐versa.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that minority ethnic groups perceive education as a pathway to upward social mobility [29,30] . Additionally, parents from working-class backgrounds exhibit middle-class aspirations and attitudes towards education, leading to significant support for their children's educational pursuits, despite their limited understanding of the education processes [31,32] .…”
Section: Socioeconomic Status Of Filipino Studentsmentioning
confidence: 99%